Avaliação de trechos de pavimentos experimentais construídos com materiais alternativos na região metropolitana de Goiânia - Marques, Michelle de Oliveira (2012)
In the Federal University of Goias (UFG) some researches have been developed focus on the importance of the alternative materials study for urban paving in substitution to the traditional materials used in the area, as the lateritic gravel. These studies contemplated the construction of experimental road pavements divided in sections in function of the materials composition used for the subbase and base layers execution, aiming the evaluation of the pavement performance when submitted to the real traffic in roads with low to medium traffic volume. Since 2004, three experimental roads were built, being two in the city of Goiania-GO and one in Aparecida of Goiania-GO. The no conventional and environmental correct materials used in those works were: civil construction waste, quarry waste, phosphogypsum and mixtures of fine soil found at the place of the work with crushed rock or lime. As the periodic monitoring is of great importance for the constant evaluation of the behavior of those pavements, this research had as objective monitors the existent roads in the year of 2011 and to compare the results obtained with the one of the previous studies. For so much, several field tests were done in two different periods: one of dry and other rainy. The field tests were executed with the following equipments: Benkelman beam, plate bearing, Dynamic Cone Penetrometer (DCP) and PenetrometreAutonomeNumeriqueDynamique equal AssistéOrdinatur (PANDA), so much with the cone of 2 cm2 as with the one of 4 cm². Besides, samples of the structural layers of the pavements and subgrades were collected for water content verification in the two periods of tests. At the end of each test the comparison of the roads performance was done along the time from the construction period. In general, it is observed that all the alternative materials used in the experimental pavements have been presenting similar behavior to the lateritic gravel, showing application viability.